Pengembangan Bahan Ajar Matematika Materi Bilangan Berbasis Higher Order Thinking Skills (HOTS) - Siti Munawaroh; I Nyoman Sudana Degeng; Nurmida Catherine Sitompul (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2021)
Development of Mathematics Teaching Materials for Numbers Based on High Order Thinking Skills (HOTS) for junior high school students is intended to provide one answer to the lack of a companion Mathematics learning companion number material that implements the 2013 curriculum and the limitations of teachers in developing HOTS-oriented learning strategies and the existence of demands for students who always accustom themselves to think critically, analytically, solve problems and increase creativity. This research uses Research and Development (R&D) research methodology where researchers limit research on a small scale, including to limit the research steps. Validation results obtained that overall design experts gave an average score of 4.7. Media experts score an average of 4.7. Mathematics teachers gave an average score of 3.84 and the student response questionnaire (small group test) received a score of 4.5 based on the data and analysis conducted which stated that this teaching material product was very suitable to be used as a companion book for HOTS-based Mathematics learning.